Determinants of the competitiveness of smallholder African indigenous vegetable farmers in high-value agro-food chains in Kenya: A multivariate probit regression analysis - Evans Ngenoh; Barnabas Kiplagat Kurgat; Hillary Kiplangat Bett; Sindu Workneh Kebede; Wolfgang Bokelmann; Fabio Gaetano Santeramo (Agricultural and Food Economics, 2019)
Smallholder farmers are excluded from efficient and effective participation in high-value agro-food market chains due to major competitiveness constraints and several market failures along these chains. The purpose of this study is to contribute to the competitiveness of smallholder farmers in a more coordinated and sustainable way that promote their effective and efficient participation in high-value agro-food market chains. In particular, the study aims at determining the main role of households' capitals, institutional, and access-related factors in conditioning the decision of smallholder farmers of African indigenous vegetables (AIVs) to access pillars of competitiveness in high-value market chains (HVMCs). For this purpose, a unique household-level data from a total of 1232 rural and peri-urban AIV-producing households were surveyed, and the data obtained were analysed by using a multivariate probit model. The results suggest that about two thirds of smallholder AIV farmers had access to at least one pillar of competitiveness in HVMCs. The model results show the presence of inter-dependency of household level decisions to access multiple pillars of competitiveness in HVMCs. Furthermore, the results also reveal that coping with shocks, coupled with access to information on market prices and warnings of unexpected events, contract farming, certification and modern irrigation technologies are the main conditioning factors to the access of the pillars of competitiveness by smallholder farmers. The promotion and implementation of a well-founded mobile phone-based information access platforms, as well as effective and efficient livelihood strategies that support smallholder farmers to access pillars of competitiveness, is of critical importance towards overcoming the major competitiveness constraints along high-value agro-food chains.
Keywords: 330